New Scheme of Intermittent Benznidazole Administration in Patients Chronically Infected with Trypanosoma cruzi: a Pilot Short-Term Follow-Up Study with Adult Patients - Alvarez, María Gabriela (2016)
Fil: Alvarez, María Gabriela. Hospital Interzonal General de Agudos Eva Perón, San Martín, Buenos Aires, Argentina.